Determining knowledge-intensive companies acquisition value for M&A purposes : an intellectual capital approach - Alves, João Marcelo (2015)
The acquisition price of knowledge-intensive companies in an M&A deal depends largely on the resultant operating synergies, i.e. the potential value knowledge companies can bring to the acquirer's existing businesses through the combination of both firms' assets. The value of knowledge companies basically resides in their innovation potential and human capital competencies. These intangibles are part of knowledge companies' intellectual capital, which is generally seen by market-established firms as the least resource- and time-consuming route to innovation. In this paper the author provides an alternative approach to valuation in order to assess the purchase price of a knowledge company in a merger or acquisition context. In particular, he analyzes the additional value a knowledge-intensive company can bring to the acquiring firm and how much of that value should be retained by the acquirer.